PERFORMANCE INVESTIGATION OF A THERMOELECTRIC COOLING SYSTEM FOR BUILDINGS - CHELLIAH, EDWIN RAKESH (IRC, 2018)
Cooling systems for buildings account for a large portion of energy consumption that of late has demanded greater use of green energy. Thermoelectric modules (TEMs) are solid state energy converters that do not require the use of working fluids. Usage of TEMs are would reduce the Ozone Depletion Potential (ODP) as well as Global Warming Potential (GWP) of the cooling system as compared to usage of Freon and other refrigerants. his project aims to assemble and install a thermoelectric air duct as well as experiment and optimise the performance of the Thermoelectric Cooling System with varying current supply to the Thermoelectric modules, air flow rate of the cold side and height of heat dissipating fans from the heat sink for space conditioning of buildings in tropical climate. The optimised system has a current supply to the Thermoelectric modules of 1.4 A, cold side fan speed of 1.67 m/s and hot side fan height of 0 cm from the heat sink and was setup in a test room to study the performance of the system in tropical climate. The setup yielded a cooling capacity of 41.62 W and a Coefficient of Performance of 1.21. These parameters should be taken into consideration when designing a Thermoelectric cooling system for buildings.